Kinematic analysis and tertiary evolution of the Lesvos ophiolites and metamorphic sole (Aegean sea, Greece) - MOUNTRAKIS, D.; THOMAIDOU, E.; ZOUROS, N.; KILIAS, A. (Bulletin of the Geological Society of Greece, 2001)
In Lesvos Island, the ophiolites and the metamorphic sole are emplaced onto the Permo-Triassic continental margin rocks. New field data on the Tertiary kinematics distinguished three successive tectonic events that affected the Lesvos ophiolites and sole. The Dl compressional event took place in Late Eocene - Early Oligocene and produced several thrust sheets and their stacking over the continental margin. The thickening of the crust after the Dl event, was followed by an important extensional tectonic event (D2) in semi-ductile conditions in Oligocene-Early Miocene times, which produced the uplift process of the orogen and the lateral rejection of the tectonic nappes through large extensional semi-ductile faults of low angle (detachment faults) and caused the exhumation of the underlying continental margin rocks in the form of a tectonic window. This extensional tectonic event led to the thinning of the crust in the wider area of Lesvos and probably caused the Early Miocene volcanic activity. The last D3 extensional tectonic event, took place in brittle conditions and represents the neotectonic regime in Late Miocene-Recent times.